Efficiency and resource implications of food losses and waste in sub-Saharan Africa - Aragie, Emerta A. (SAGE Publications, 2022)
Reducing the huge level of food losses and waste is arguably one of the sustainable ways of closing the food requirement gap in developing countries. Examining selected sub-Saharan Africa countries and utilizing the Food and Agriculture Organization of the United Nations’ Food Balance Sheet data, this study suggests that these countries lose over 29% (58.8 million tons) of the primary equivalent component of food. Exploiting the rich data on water and land footprints of food commodities, this study also identified considerable losses in resources – 21% of total water use and 15% of cropland use – associated with the food supply chain losses, with noticeable implications for agricultural sustainability.